CEO Compensation around the World - Pereira, Ivo; Esperança, J.; Curto, J. (XIII I - Iberiam International Busiiness Conference, 2017)
Although much attention has been devoted to managerial compensation, most empirical studies have been country specific or limited to a small number of countries. This is mainly due to the scarcity of available data on countries with fewer shareholder protection mechanisms. By focusing on chief executive officer (CEO) compensation, and using the more comprehensive information available on 997 firms worth more than €1 billion, we shed new light on the determinants of CEO compensation. As compared to other studies, we focused more on country and industry effects and related types of ownership, contrasting these with the usual performance and size variables. The findings demonstrate a negative relationship between firm performance and CEO compensation, suggesting that executives place self-interest above the interests of their firms. Furthermore, we found that expatriated CEOs and CEOs in Anglo-Saxon firms attain higher levels of compensation.